Clinical Evaluation of CyberKnife in the Treatment of Vestibular Schwannomas. (10th November 2013) - Tsai, Jo-Ting; Lin, Jia-Wei; Lin, Chien-Min; Chen, Yuan-Hao; Ma, Hsin-I; Jen, Yee-Min; Chen, Yi-Hsun; Ju, Da-Tong
Abstract : Objective . This study assessed the posttreatment tumor control and auditory function of vestibular schwannoma (VS) patients after CyberKnife (CK) and analyzed the possible prognostic factors of hearing loss. Methods . We retrospectively studied 117 VS patients, with Gardner-Robertson (GR) classification grades I to IV, who underwent CK between 2006 and 2012. Data including radiosurgery treatment parameters, pre- and postoperative tumor size, and auditory function were collected and examined. Results . With CK, 117 patients had excellent tumor control rates (99.1%), with a mean imaging followup of 61.1 months. Excluding 52 patients (GR III-IV pretreatment), 53 (81.5%) of the remaining 65 patients (initial GR I-II) maintained GR I or II hearing after CK, with a mean audiometric followup of 64.5 months. Twelve patients experienced hearing degradation (91.6% were GR II pretreatment); they appeared to have significantly larger tumor sizes, significantly smaller cochlear sizes, and higher prescribed cochlear doses, compared to the patients with preserved hearing. Conclusion . Our data showed that CK treatment provided an excellent tumor control rate and a comparable hearing preservation rate in VS patients. Patients with pretreatment GR II hearing levels, larger tumor volumes, smaller cochlear sizes, and higher prescribed cochlear doses may have poor hearing prognoses.